(untitled) (Journal of Namibian Studies : History Politics Culture, 2023)
The Emergency was a twenty-one months period from 1975 to 1976 during which Prime Minister Indira Gandhi ruled by decree. It was declared by President Fakhruddin Ali Ahmed due to internal disturbances. Indira Gandhi started an aggressive program in 1976-77 to control population growth by sterilizing men and women. The government was forced to adopt such policies because the funding nations and agencies like the World Bank, the Swedish International Development Authority and the UN Population Fund threatened to stop granting funds to India. Indira Gandhi along with his son Sanjay Gandhi tried to control population growth with gruesome measures which in history is described as the dark days.